Effects of sildenafil citrate on torsion/detorsion-induced changes in red blood cell and plasma lipid peroxidation, antioxidants, and blood hematology of male rats - Yildiz, Hamit; Durmus, Ali Said; Simsek, Halil; Yaman, Ihsan (Elsevier, 2011)
Objective: The aim of this work was to determine effects of intrapertoneally-administered sildenafil citrate (SC) for prevention testicular injury after unilateral testicular torsion/detorsion (T/D) in rats on red blood cell (RBC) and plasma lipid peroxidation, antioxidants and blood hematology. Study design: Thirty seven adult male wistar albino rats were divided into four groups: sham operated (group 1), T/D + saline (group 2), T/D + 0.7 mg SC (group 3) and T/D + 1.4 mg SC (group 4). Testicular torsion was created by rotating the right testis 720 in a clockwise direction for 2 h in all the groups, except for group 1. Results: Our results showed that that testicular injury significantly induced erythrocyte reduced glutathion (GSH) (p < 0.05), malondialdehyde (MDA) in RBC (p < 0.01) and plasma (p < 0.05) and blood lymphocyte (p < 0.01) counts. Administration of low dose SC led to significantly increase in the levels of RBC GSH (p < 0.05), plasma paraoxonase (PON1)(p < 0.01), nitric oxide (NO) (p < 0.01) and blood lymphocyte counts (p < 0.01), but to decreases in the levels of MDA in plasma and RBC, blood mean corpuscular volume (MCV) (p < 0.05) and eosinophil counts (p < 0.05). Treatment with high dose SC caused a significantly increase in PON1, vitamin E and beta-carotene in plasma, levels of GSH in RBC and blood lymphocyte counts. On the other hand, results showed that high dose sildenafil significantly decreased plasma and RBC MDA levels. Total tissue damage scores of the group 2 were significantly higher than group 1 and 3. Conclusion: Low dose SC appears to be beneficial in reducing the effects of injury to the testicular torsion. (C) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: Testicular torsion; Biochemical; Hematology; Sildenafil citrate